RSV frequency in children below 2 years hospitalized for lower respiratory tract infections - Hacımustafaoğlu, Mustafa; Celebi, Solmaz; Bozdemir, Sefika Elmas; Ozgür, Taner; Ozcan, Ismail; Güray, Atilla; Cakır, Deniz (The Turkish Journal of Pediatrics, 2013)
Respiratory syncytial virus (RSV) is the most frequent agent of acute lower respiratory diseases and creates a significant burden of disease in children under 5 years all over the world. RSV causes severe lower respiratory tract infections (LRTI) that require hospitalization, especially in children ≤2 years. The aim of this study was to determine the incidence of RSV in children ≤2 years of age hospitalized for LRTI. Children ≤2 years of age hospitalized for one year for LRTI in the three largest hospitals of Bursa City Center, Turkey were evaluated. These three hospitals comprise 67.5% of all child beds in central Bursa, so this study allows us to evaluate the total disease burden and hospitalization incidence in central Bursa. Nasal swabs of the children were evaluated with RSV Respi- Strip (Coris Bioconcept Organization). A total of 671 children were hospitalized for LRTI, and 254 (37.9%) had at least one hospitalization that was positive for RSV. Of all patients with LRTI, 54.8% (368/671) were hospitalized for acute bronchiolitis, while 45.2% (303/671) were hospitalized for pneumonia. Of patients with acute bronchiolitis or pneumonia, 41% (151/368) and 34% (103/303) were RSV+, respectively. Of RSV+ hospitalized children, 59.5% (151/254) were diagnosed as acute bronchiolitis and 40.5% (103/254) as pneumonia. The annual incidences of hospitalization due to LRTI, acute bronchiolitis and pneumonia were 20.5/1000, 11.2/1000 and 9.3/1000, respectively, in children ≤2 years of age. The annual incidences of hospitalization due to RSV+ LRTI, acute bronchiolitis and pneumonia were found as 7.8/1000, 4.6/1000 and 3.2/1000, respectively, in children ≤2 years of age. More than one-third of all children hospitalized with LRTI (38.3%, n=257) were in the 0-3 months age group. Compared to other age groups, RSV positivity was highest in that age group for acute bronchiolitis (57%), pneumonia (39.5%) and also total children with LRTI (47.9%). RSV is a very important cause of lower respiratory infections in children ≤2 years of age and occurred most frequently in those 0-3 months of age in our study. Since there is no other study assessing the annual hospitalization incidence of RSV+LRTIs in one city in Turkey, our study has unique importance for providing valuable statistical data about RSV+LRTIs.